Odins viden - dens funktion og betydning - Schjødt, Jens Peter (Religionsvidenskabeligt Tidsskrift, 2004)
it is the purpose of this article to discuss how to interpret Odin's wisdom. Many scholars have argued over the last ten years that Odin's wisdom should be compared to the abilities of the shaman as this figure is known from many circumpolar religions and that Odin should accordingly be viewed as a prototypical shaman. There are, however, some arguments against this theoy. First and foremost, it is obvious that Odin has certain functions in old Norse mythology that do not fit in with the "shamanic" interpretation. If we take a closer view of the role of Odin, it is obvious that he is not primarily linked to the magicians but rather to warriors and kings. This is due to the fact that shamans are normally practicing in societies very different from those of Scandinavia during the Viking age. The results of two analyses of mythical cores, that of Mimer, primarily known from the Eddas, and that of Hadding, known from Saxo's Gesta Danorum, show that a religious phenomenon explaining more adequately the many roles of Odin is that of initiation. The Mimer myth shows how Odin acquires intellectual power by confronting an object (the head of Mimer) which has been in the under world where is has been given numious poser. This myth is compared to the phenomenon of initiation and it is maintained that the myth, containing death and intellectual rebirth, must be seen as parallel in its structure as well as its symbolism to the initiation rituals which we see all over the world. Odin has thus gained knowledge as all initiates do during their initiation. On the other hand, the Hadding myth shows us Odin in a different role which is known equally well in the context of the mythology, namely that as an initator giving advice and skills to the young hero of the myth. Here we find the same symbolism as that of the initiation. Eventually, it is concluded that even if many of Odin's skills may be compared to those of the shaman, the phenomenon of initiation is able to account for the whole spectrum of functions that can be seen in Odin. Odin, then, must be seen first and foremost as the god of initiation.